Risk Factors for Mortality Among Confirmed Covid-19 Patients At RSUP Dr.Kariadi - Junaedi, Husain; Pramudo, Setyo Gundi; Bhima, Sigid Kirana Lintang; Dhanardono, Tuntas (Medica Hospitalia : Journal of Clinical Medicine, 2023)
BACKGROUND: Coronavirus Disease 2019 (COVID-19) is a communicable disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). On March 11, 2020 the World Health Organization (WHO) declared COVID-19 as pandemic causing mortality in more than 150 countries. China reports the most case is among people aged 30 – 79 years old and male, meanwhile in Italia the most case is among patients with cardiovascular disease, diabetes, chronic diseases, hypertension, and cancer. This encourages researcher to examine risk factors causing mortality among patients with confirmed COVID-19. METHOD: This is an observational study with multivariate analytical test. The samples involved medical records of died patients with confirmed COVID-19 at RSUP Dr.Kariadi. Risk factors being studied involved age, gender and comorbidities such as hypertension, diabetes, pneumonia, chronic obstructive pulmonary disease (COPD), heart disease, kidney disease, and cancer. Data were analyzed using multiple logistic regression with univariate, bivariate, multivariate, confounding and interaction tests. RESULT: An increased risk for mortality was found among confirmed COVID-19 patients aged over 60 years (3.25 times), suffered from hypertension (2.09 times), pneumonia (4.77 times), cancer (11.89 times), heart disease (3.55 times), and kidney disease (5.23 times). CONCLUSION: Risk factors involving age, hypertension, pneumonia, cancer, heart disease, and kidney disease increase risk for mortality among patients with confirmed COVID-19. The risk is heightened as patients aged older than 60 years old suffering from pneumonia and cancer simultaneously.